2017
DOI: 10.24884/1682-6655-2017-16-2-17-24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of problems in the rehabilitation diagnosis in the categories of the international classification of functioning in patients with stroke taking part in the pilot project «Development of the system of medical rehabilitation in Russia»

Abstract: Одной из главных составляющих реабилитации является постановка реабилитационного диагноза [7, 8]. Корректный реабилитационный диагноз дает исчерпывающее представление о состоянии пациента, указывает на основные проблемы, имеющиеся возможности-что умеет пациент делать и чего не может в результате заболевания, что актуально для него и какие люди принимают участие в реабилитационном процессе [7]. Таким образом, реабилитационный УДК 615.83

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 9 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…ere was no significant difference in each time period. e instability of the knee joint will cause damage to the medial meniscus [8]. e incidence of medial meniscus injuries within 3 months of anterior cruciate ligament rupture is about 30%; medial meniscus injuries lose 3 in the anterior cruciate ligament.…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…ere was no significant difference in each time period. e instability of the knee joint will cause damage to the medial meniscus [8]. e incidence of medial meniscus injuries within 3 months of anterior cruciate ligament rupture is about 30%; medial meniscus injuries lose 3 in the anterior cruciate ligament.…”
Section: Complexitymentioning
confidence: 99%
“…Foreign scholars have reported that in animal experiments, the position of the ACL tibial plateau on the tibial plateau was moved forward and backward, and the tibial plateau and knee stability were significantly different, suggesting the position of the tibial plateau and its restrictions [5]. e ability of the tibia to move forward and maintain the stability of the knee joint is closely related, but there is still no research report on the clear correspondence between the position of the ACL tibial stop and the ACL control force [6][7][8][9]. e connection point between the ligament and the bone is not a simple ligament bone connection, but a complex structure.…”
Section: Introductionmentioning
confidence: 99%